Image Search Engine of Mono Image - Mohammed Ali; Asmaa Salah Aldin Ibrahim (IJRDO -Journal of Computer Science Engineering, 2019)
In recent year, images are widely used in many applications, such as facebook, snapchat. The large numbers of these images are saved in the smart system to easy access and retrieve. This paper aims to design and implement the new algorithm which is used in search of images. The mono image (black and white) is used as input data to the proposed algorithm. The methodology of this paper is to split image into number of block (block size = 8*8). For each block set 1 or 0 in order to count the number of black and white pixels. Finally, the result compare with other image dataset with the threshold value. The result show’s that the proposed algorithm is successful passed in tested stage.